Guide :

Simplify 6x-4x+8-5

Simplify the question.

Research, Knowledge and Information :


How do I simplify 6x+8/4x+4? - Brainly.com


How do I simplify 6x+8/4x+4? 2. Ask for details ; Follow; Report; by anaborgen 04/21/2017. Log in to add a comment ... 5 points 8 minutes ago
Read More At : brainly.com...

How to simplify the expression sqrt(4x^8) - Quora


How do I simplify the expression sqrt(4x^8)? Update Cancel. Answer Wiki. 2 Answers. ... How do I simplify the expression? What does it mean to simplify an expression?
Read More At : www.quora.com...

Mathway | Solve for x 5/6x-4x+8/3=5/3


Precalculus Examples. Popular Problems. Precalculus. Solve for x 5/6x-4x+8/3=5/3. Simplify the left side. ... Simplify the left side of the equation by cancelling the ...
Read More At : www.mathway.com...

How do you simplify (4x+8) /( 3x)* (9x^2) / (x+2)? | Socratic


... (4x+8)/(3x) * (9x^2)/(x+2) You can simplify this expression by factoring the ... The numerator of the first fraction can be rewritten as 4x+8 = 3 ... (6x )/10*(6x ...
Read More At : socratic.org...

How do you simplify ((6x^4y^8)^3)/(4x^4y^10)? | Socratic


How do you simplify #((6x^4y^8)^3)/(4x^4y^10)#? Algebra. 4 Answers ? 1 Jim G ...
Read More At : socratic.org...

Simplify. 7x + 3(x - 2) - 4x + 8 A) 6x + 2 B) 6x + 14 C) 6x ...


Simplify. 7x + 3(x - 2) - 4x + 8 A) 6x + 2 B) 6x + 14 C) 6x - 2 D) ... The simplified equation would be 6x-6+8 and then it ... Simplify open parentheses x to the 2 ...
Read More At : brainly.com...

Simplifying and Combining Like Terms - SFP Online


Simplify: 1) 7x + 5 – 3x 2) 6w2 ... + 5(4x – 7) 6) 6(15 – 6x ) + 11(4x – 8) 7) 3(12x – 4) – 5(8x + 7) 8) 4(8x + 5) ... Simplifying and Solving Equations ...
Read More At : www.sfponline.org...

Algebra Questions with Solutions and Explanations for Grade 9


Algebra Questions with Solutions ... Group like terms and simplify. - 6x + 5 + 12x -6 = (- 6x + 12x) + (5 ... 6x - 8 = 4x + 4 4(x - 2) = 2(x + 3) ...
Read More At : www.analyzemath.com...

Suggested Questions And Answer :


8×?=(?×8)+(4×8)

If the question mark means the same on each side of the equation then there is no solution because the equation is false. 8 x ? = ? x 8 in normal multiplication, because the order of the multiplicands doesn't matter. So we're left with 0=4x8 which isn't true. The brackets don't make any difference because the priority rules put multiplication before addition. If the question marks mean something different on each side of the equation, then we have a relationship or linear equation for which there are an infinite number of solutions: 8y=8x+32, effectively. This simplifies to y=x+4. This can be represented by a straight line for which each point on the line is a solution. A third alternative speculates that "x" does not mean multiply so that 8x? does not mean the same as ?x8. An example would be that x means divide, where the order of the operands matters. But then we're left to speculate what + means, opening the way to endless possibilities.    
Read More: ...

sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 times. 3a+10=(~(2a-1)+2)(~(2a-1)+2) Multiply each term in the first group by each term in the second group using the FOIL method. FOIL stands for First Outer Inner Last, and is a method of multiplying two binomials.  First, multiply the first two terms in each binomial group.  Next, multiply the outer terms in each group, followed by the inner terms.  Finally, multiply the last two terms in each group. 3a+10=(~(2a-1)*~(2a-1)+~(2a-1)*2+2*~(2a-1)+2*2) Simplify the FOIL expression by multiplying and combining all like terms. 3a+10=(~(2a-1)^(2)+4~(2a-1)+4) Remove the parentheses around the expression ~(2a-1)^(2)+4~(2a-1)+4. 3a+10=~(2a-1)^(2)+4~(2a-1)+4 Raising a square root to the square power results in the expression inside the root. 3a+10=(2a-1)+4~(2a-1)+4 Add 4 to -1 to get 3. 3a+10=2a+3+4~(2a-1) Since a is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 2a+3+4~(2a-1)=3a+10 Move all terms not containing ~(2a-1) to the right-hand side of the equation. 4~(2a-1)=-2a-3+3a+10 Simplify the right-hand side of the equation. 4~(2a-1)=a+7 Divide each term in the equation by 4. (4~(2a-1))/(4)=(a)/(4)+(7)/(4) Simplify the left-hand side of the equation by canceling the common terms. ~(2a-1)=(a)/(4)+(7)/(4) To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(2a-1))^(2)=((a)/(4)+(7)/(4))^(2) Simplify the left-hand side of the equation. 2a-1=((a)/(4)+(7)/(4))^(2) Combine the numerators of all expressions that have common denominators. 2a-1=((a+7)/(4))^(2) Expand the exponent of 2 to the inside factor (a+7). 2a-1=((a+7)^(2))/((4)^(2)) Expand the exponent 2 to 4. 2a-1=((a+7)^(2))/(4^(2)) Simplify the exponents of 4^(2). 2a-1=((a+7)^(2))/(16) Multiply each term in the equation by 16. 2a*16-1*16=((a+7)^(2))/(16)*16 Simplify the left-hand side of the equation by multiplying out all the terms. 32a-16=((a+7)^(2))/(16)*16 Simplify the right-hand side of the equation by simplifying each term. 32a-16=(a+7)^(2) Since (a+7)^(2) contains the variable to solve for, move it to the left-hand side of the equation by subtracting (a+7)^(2) from both sides. 32a-16-(a+7)^(2)=0 Squaring an expression is the same as multiplying the expression by itself 2 times. 32a-16-((a+7)(a+7))=0 Multiply -1 by each term inside the parentheses. 32a-16-a^(2)-14a-49=0 Since 32a and -14a are like terms, add -14a to 32a to get 18a. 18a-16-a^(2)-49=0 Subtract 49 from -16 to get -65. 18a-65-a^(2)=0 Move all terms not containing a to the right-hand side of the equation. -a^(2)+18a-65=0 Multiply each term in the equation by -1. a^(2)-18a+65=0 For a polynomial of the form x^(2)+bx+c, find two factors of c (65) that add up to b (-18).  In this problem -5*-13=65 and -5-13=-18, so insert -5 as the right hand term of one factor and -13 as the right-hand term of the other factor. (a-5)(a-13)=0 Set each of the factors of the left-hand side of the equation equal to 0. a-5=0_a-13=0 Since -5 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 5 to both sides. a=5_a-13=0 Set each of the factors of the left-hand side of the equation equal to 0. a=5_a-13=0 Since -13 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 13 to both sides. a=5_a=13 The complete solution is the set of the individual solutions. a=5,13
Read More: ...

Find m if x – 3 and x + 2 are factors of x3 + m2x2 – 11x – 15m

  36r4 + 36r3 + 3r2) / 9r3  this is normally written as (36r^4 + 36r^3 + 3r^2) / (9r^3)  this is equivalent to (36r^4 / 9r^3) + (36r^3 / 9r^3) + (3r^2 / 9r^3)  the rule for exponent arithmetic to apply is that x^a/x^b = x^(a-b).  so, basically, if the base is the same, then you subtract the exponent in the denominator from the exponent in the numerator and put the result in the numerator.  the other rule for exponent arithmetic to apply is that x^-a = 1/x^a.  you take the reciprocal and change the sign of the exponent.  x^-a = 1/x^a  x^a = 1/x^-a  normally you want to simplify by making all the exponents positive, so if you have x^-a, then show it as 1/x^a, and if you have 1/x^-a, then show it as x^a.  looking at each of the parts of (36r^4 / 9r^3) + (36r^3 / 9r^3) + (3r^2 / 9r^3) individually, you get:  36r^4 / 9r^3 becomes 36/9 * r^4/r^3 which becomes 4 * r^(4-1) which becomes 4r^1 which becomes 4r.  36r^3 / 9r^3 becomes 36/9 * r^3/r^3 which becomes 4 * r^(3-3) which becomes 4 * r^0 which becomes 4 * 1 which becomes 4.  3r^2/9r^3 becomes 3/9 * r^2/r^3 which becomes 1/3 * r^(2-3) which becomes 1/3 * r^-1 which becomes 1/3 * 1/r^1 which becomes 1/3 * 1/r which becomes 1/(3r)  your simplified expression becomes 4r + 4 + 1/(3r)  this should be your solution, but if you wanted to put everything under the same denominator, then you would get:  4r + 4 + 1/(3r) becomes (4r*3r + 4*3r + 1) / (3r)  simplify this to get:  (12r^2 + 12r + 1) / (3r)  that should be your simplified expression.  if we did this correctly, your original expression and your simplified expression should give you the same answer if you replace r with a random value.  for example, assume r = 7  your original expression of (36r^4 + 36r^3 + 3r^2) / (9r^3) becomes equal to 32.04761905  your simplified expression of (12r^2 + 12r + 1) / (3r) becomes equal to 32.04761905  since they both provide the same answer, they're equivalent and you can reasonable conclude that you simplified correctly.  if your stated solution is not this, then let me know what it is and i'll come up with a reason why it should be that and not what i just told you.  the difference, if any, is usually in what the definition of simplified is.   
Read More: ...

how do i add fractions

To add or subtract fractions, obtain a least common denominator. Subtract the numerators in the correct order and retain the same least common denominator for your answer. Simplify. To multiply fractions, multiple the numerators. The product will be the numerator of your answer. Repeat with denominators. Simplify. To divide fractions, take the reciprocal of what you are dividing by. Multiply the reciprocal with the initial number (see above for multiplication process). Simplify. Evaluate means to solve. You can solve fraction problems using the above processes. You can only simplify if both the numerator and denominator are divisible by the same number. If the denominator is odd, you can only simplify it if the numerator also is divisible by a same number. Ex. 88/33. Although the denominator is odd, both the numerator and denominator are divisible by 11 resulting in 8/3 as the simplified answer. To pace yourself during a test do the following. Find out how long you have for the test. Divide this by the total number of problems on the test. Example. 1 hour for 20 problems on your test. This means you have 3 minutes per problem. If you spend more than 3 minutes on a problem, skip it. Continue until you attempt all the problems. Go back with the remainder of the time to retry these problems you skipped. Most likely they are the most difficult, hence why you spent alot of time on them. This method of pacing allows you to skip the hard problems at first, attempt all problems, and finish the easier problems for sure.
Read More: ...

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}
Read More: ...

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}
Read More: ...

Expand and simplify where appropriate

[r-36(p.q+q)/3] simplifies to [r-12q(p+1)] or [r-12pq-12q]. {n+r[r-36(p.q+q)/3]+p} therefore simplifies to {n+r[r-12pq-12q]+p}={n+r^2-12pqr-12qr+p}. m{ ... } simplifies to mn+mr^2-12mpqr-12mqr+mp. Finally, multiply by 3q/p: 3mnq/p+3mqr^2/p-36mq^2r-36mq^2r/p+3mq.
Read More: ...

simplify this expression 9(a+b)

simplify 9(a+b) It's already simplified. 9(a+b) simplified is 9(a+b) if you mean expand 9(a+b) that's 9a + 9b
Read More: ...

2x/3+1/4=9,find x

2x/3+1/4=9 (2x)/(3)+(1)/(4)=9 Since (1)/(4) does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting (1)/(4) from both sides. (2x)/(3)=-(1)/(4)+9 Simplify the right-hand side of the equation. (2x)/(3)=(35)/(4) Multiply each term in the equation by 3. (2x)/(3)*3=(35)/(4)*3 Simplify the left-hand side of the equation by canceling the common terms. 2x=(35)/(4)*3 Multiply (35)/(4) by 3 to get (105)/(4). 2x=(105)/(4) Divide each term in the equation by 2. (2x)/(2)=(105)/(4)*(1)/(2) Simplify the left-hand side of the equation by canceling the common terms. x=(105)/(4)*(1)/(2) Simplify the right-hand side of the equation by simplifying each term. x=(105)/(8)
Read More: ...

How to simplify fractions

When simplifying fractions we need to reduce both the numerator (the number on the top of the fraction) and the denominator (the number on the bottom of the fraction) so that both numbers have no common factors (numbers that can be evenly divided into both) Let's take this the example 30/100 We need to find the greatest common factor of 30 and 50 and then divide both numbers by the greatest common factor.  Let's list all of the numbers that go into 30 and 100 2, 5, 10 10 is the greatest common factor.  Divide both 30 and 100 by 10 to get the simplified fraction 3/5 This is the simplified form.
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.math-problems-solved.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0603 seconds